Difficulties in learning mathematical concepts from the point of view of Teacher and Suggestions for Their Development (Journal of Hama University, 2019)
The research aimed to identifying  the difficulties of students in the learning of  mathematical concepts from the teachers ,points of view, and the number of members of the research sample was (200) who were chosen at random. The researcher prepared a questionnaire of opinions commensurate with the questions of the research and its hypotheses of the research and it has applied on the research samples after verifying of its psychometric characteristics.The research concluded the following results:1- The  are statistical significant differences between the average scores of teachers on the questionnaire according to the variable of scientific qualification.2- The  are statistical significant differences between the average scores of teachers on the questionnaire according to the variable years of experienc